2016
DOI: 10.1097/ijg.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ocular Blood Flow Between People of African and European Descent With Healthy Eyes

Abstract: Purpose: To investigate differences in ocular blood flow between people of African (AD) and European descent (ED) with healthy eyes.Methods: Retrobulbar and retinal capillary blood flow was assessed in one eye of 58 participants (24 AD, 34 ED) with healthy eyes with systemic blood pressure lower than 140/90. Retrobulbar blood flow was measured in the ophthalmic artery (OA), central retinal artery (CRA), nasal (NPCA) and temporal posterior ciliary arteries (TPCA). Peak systolic velocity (PSV), end diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(41 reference statements)
1
8
0
2
Order By: Relevance
“…One study observed lower retrobulbar flow in people of African descent than in those of European descent and suggested that this difference may be because of higher glaucoma rate in African population (Kaskan et al. ). In the present study and other studies, colour Doppler was used to measure the blood flow (Siesky et al.…”
Section: Discussionmentioning
confidence: 99%
“…One study observed lower retrobulbar flow in people of African descent than in those of European descent and suggested that this difference may be because of higher glaucoma rate in African population (Kaskan et al. ). In the present study and other studies, colour Doppler was used to measure the blood flow (Siesky et al.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler flow analysis of retrobulbar vessels using DU is a useful way to determine orbital, ocular, central nervous system, and systemic vascular pathology. For this, it is important to have normal values of MSV, EDV, and RI adjusted for the population under examination since there is evidence that shows significant changes in these values depending on the place of origin, as shown in a study that compared 24 patients of African descent and 34 patients of European descent, indicating that the latter has higher EDV and RI values, without differences in MSV in the four arteries examined 13,14 . When comparing these values with those of our sample, we observed that Mexican patients show higher flow velocities with lower RIs.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the retrobulbar vessels using DU shows that hemodynamic changes develop as the age of the patients increases, showing lower flow rates and higher resistance indices in older adult patients 8 , as a result of vessel aging with the remodeling of the intima and media layers, which leads to loss of elasticity and arterial stiffness 9,10 . In previous studies, normal values have already been determined in healthy patients in other parts of the world, such as North America 11 and the United Kingdom 12 , and other researchers have found that there are hemodynamic variations in orbital circulation assessed by DU among patients with different ethnic origins, mainly between Europeans and Africans, and have concluded that the lower flow rates in Africans may imply a mechanism that increases the risk of glaucoma 13,14 . The systolic and diastolic flow velocities and the resistance indices in the retrobulbar vessels depend on multiple factors, and therefore the different pathologies that affect them will reflect the variability of the vascular hemodynamic parameters determined in the evaluation with DU 15 .…”
Section: Introductionmentioning
confidence: 98%
“…Inclusion and exclusion criteria are described in detail elsewhere. 16 All study procedures conformed to the tenets of the Declaration of Helsinki and were approved by the Institutional Review Board at Indiana University School of Medicine. All subjects signed an informed consent prior to entry into the study.…”
Section: Methodsmentioning
confidence: 99%
“…15 Lower blood flow in retrobulbar vessels has been reported in the healthy eyes of AD compared to ED. 16 A missing element in understanding vascular contributions to the POAG process could be an established knowledge of blood flow changes over the course of development and with aging. Therefore, developing a normative database and baseline parameters is important with regard to studying racial differences in the development of POAG.…”
Section: Introductionmentioning
confidence: 99%